The teaching of cross-cultural skills in the english language classroom. - Darquea, Ambar (2010)
The present investigation emphasizes the importance of teaching cultural aspects in english lessons in order to improve the level of communicative and sociocultural competence of the students. Many linguists have agreed in saying that a language cannot be learnt isolated from its correspondent culture. In that case, I decided to focus my study on the teaching of american culture, considering that there are major possibilities of having a student visiting the United States, instead of going farther to a european english speaking country. Previous investigations on this same theme had been done in some parts of the european continent, but here in our country, and especially in Riobamba, it is the first time that a study like this one has been carried out. It consisted of interviews and questionnaires for students and teachers belonging to private and public schools. The first part of this thesis will show the statistical results. Next, an analysis will be presented in order to see if culture is taught in the english classrooms. Finally, a proposal will then be established in order to incorporate the teaching of the American culture in the english curriculum.